Key parameters and efficiency of Mexican manufacturing: Are there still differences between the north and the south? An application of nested and stochastic frontier panel data models - Frauke G. Braun; Astrid Cullmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This study explores the prevalence and nature of the regional divide for the Mexican manufacturing production across sub-national regions. We utilize a unique panel of municipality-level data from the manufacturing sector. An important contribution is the use of different panel methods to account for latent regional characteristics and the computation of performance indicators for each municipality which will enable detailed regional rankings. Firstly, we apply nested panel methods to estimate regional production functions and to analyze production characteristics and scale economies. Subsequently, we use stochastic frontier analysis methods to test for productivity and efficiency differences in manufacturing throughout the country. Our results suggest that the economic structure and productivity of southern Mexico is considerably different from the centrally located manufacturing belt and the north. Remarkably, rankings based on nested panel and stochastic frontier estimations confirm very similar regional patterns. Nevertheless, efficiency varies strongly within states, indicating that 'islands of excellence' prevail in otherwise highly inefficient and lagging states.
Keywords: C23; D24; O18; 330; Mexico; manufacturing; efficiency analysis; stochastic frontier analysis; panel data models; Verarbeitendes Gewerbe; Produktivität; Wirtschaftliche Effizienz; Technische Effizienz; Regionale Disparität; Panel; Mexiko